Hydraulic resistance due to vortex generated transverse oscillations in a submerged random array of circular cylinders. Issue 2 (3rd May 2016) - Chakraborty, Paromita; Patnaik, Rosalini; Sarkar, Arindam
Abstract: Experiments were conducted to estimate the drag coefficient for a random array. Typical transverse surface oscillations were observed within the array for a particular range of Reynolds number. The oscillatory flow mechanism is well described using Roshko number, which is constant during the vortex lock on. An analytical model is proposed to estimate the coefficient of drag experienced by the circular cylinders within the random array due to these transverse surface oscillations. The drag coefficient for the random array is found to be much higher in comparison to the reported values for the regular array. The drag coefficient is also calculated using Ergun equation and compared with the experimental results. The corrections due to side wall and bed are negligible for low Reynolds number regime. Also, it is found that the drag coefficient decreases with an increase in relative flow depth.